Sexual acquisition of HIV infection after solid organ transplantation: Late presentation and potentially fatal complications. Issue 4 (17th April 2018) - Cristelli, M.P.; Mazolin, M.A.; Manzardo, C.; Ribeiro, M.S.J.; Cofán, F.; Santos, D.W.C.; Castel, M.A.; Tedesco‐Silva, H.; Moreno, A.; Diekman, F.; Miro, J.M.; Medina‐Pestana, J.O.
Abstract: Introduction: While the growing knowledge on HIV among solid organ transplant recipients (SOT) is limited to either pretransplant infection or allograft transmission, there are only sparse reports describing HIV‐infection after transplantation through sexual route, the primary mode of transmission in the general population. Methods: From two different centers, we report nine new cases of HIV infection in SOT recipients attributed to sexual acquisition: eight cases of kidney‐transplant recipients and one heart‐transplant recipient. Findings: There were nine cases of post‐transplant HIV‐infection detected among 14 526 transplants performed 1998 to 2015. In 6/9 cases, infection was contracted 5 years after SOT. All but one patient had stable allograft function under immunosuppressive therapy. The main trigger to diagnosis was late CMV disease and sexually transmitted diseases; five patients had CDC‐stage 3 HIV infection. In 7/9 patients, virologic response and CD4 recovery were achieved within 3 months after starting antiretroviral therapy (ART). After an average of 3.6 years post diagnosis, 5/9 patients remained alive with well‐controlled infection and functioning allograft. Conclusion: Sexual acquisition of HIV infection after SOT represents a difficult challenge, as it may occur in any kind of transplant and at any time. The course of infection resembles that of the general population, with life‐threatening infectious complications, but good response to ART. Assessment of lifestyle and risk behavior is paramount, as indications may be not disclosed without direct questioning.